Porous ceramic particle
By preparing porous ceramic particles containing alumina and silicon oxide for annealing media, the problem of insufficient performance of existing ceramic hollow sphere materials in the annealing process is solved, and the stability and health and safety under high temperature conditions are achieved, which is improved. Product quality and service life.
Patent Information
- Application Number
- CN202410937690.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2024-07-12
- Publication Date
- 2025-01-14
AI Technical Summary
The ceramic hollow sphere materials used in existing annealing processes have room for improvement in mechanical properties, thermal conductivity and health indicators, affecting product quality and service life, and may increase health risks.
Provide a porous ceramic particles with a suitable content of aluminum oxide and silicon oxide, and form a material with good mechanical properties, thermal conductivity and health indicators through heat treatment, which is used for annealing media to ensure performance stability under high temperature conditions.
It improves the quality and service life of the annealing process products, reduces health risks, ensures the good performance of porous ceramic particles at high temperatures, and is suitable for the preparation of metal and non-metallic materials.
Smart Images

Figure CN119306477A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic materials, and in particular to porous ceramic particles. Background Art
[0002] Annealing process is one of the key links in the preparation of many materials (for example, metal materials, non-metallic materials, etc.). In the prior art, the annealing medium used in the annealing process is usually a material such as a ceramic hollow sphere, and its mechanical properties, thermal conductivity, or health indicators need to be further improved. Summary of the invention
[0003] The purpose of the present application is to provide a porous ceramic particle, which is suitable for the annealing process in the material preparation process, and still has good performance (for example, mechanical properties, thermal conductivity and health indicators, etc.) under high temperature conditions, thereby ensuring the product quality of the annealing process, and also having an improved service life, and can also help reduce health risks, etc.
[0004] To this end, the present application provides, on one hand, a porous ceramic particle, comprising:
[0005] Alumina, wherein the content of the alumina is not less than 40 wt.% based on the total weight of the porous ceramic particles;
[0006] Silicon oxide, wherein the content of the silicon oxide is not more than 55 wt.% based on the total weight of the porous ceramic particles;
[0007] The porosity of the porous ceramic particles is not greater than 60 v / v%.
[0008] In another aspect, the present application provides a method for preparing the porous ceramic particles, comprising the following steps:
[0009] S1: providing precursor particles;
[0010] S2: Heat treatment.
[0011] In another aspect of the present application, there is provided use of the porous ceramic particles as an annealing medium.
[0012] In another aspect, the present application provides an annealing medium, comprising the porous ceramic particles mentioned above. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art by referencing the accompanying drawings.
[0014] Figure 1 An electron micrograph of a cross section of an exemplary Control Sample 1 is included.
[0015] Figure 2 An optical microscope photograph of a cross section of exemplary Sample 2 is included. DETAILED DESCRIPTION
[0016] General Definitions and Terminology
[0017] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.
[0018] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by those skilled in the art to which this application belongs. In the event of a conflict, the definitions provided in this application shall prevail.
[0019] Unless otherwise stated, all percentages, parts, ratios, etc. are by weight. When a quantity, concentration, or other value or parameter is given as a range, a preferred range, or a preferred upper and lower limit, or a specific value, it should be understood as specifically disclosing all ranges formed by paired values from any upper range or preferred value and any lower range or preferred value, regardless of whether the range is disclosed individually. Unless otherwise stated, when the application quotes a numerical range, the range is meant to include its endpoints, as well as integers and fractions within all such ranges.
[0020] The terms "about" and "approximately" when used with a numerical variable generally refer to the value of that variable and all values of that variable are within experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.
[0021] The terms "comprises", "includes", "has", "contains" or "involves" and other variant forms thereof in this application are inclusive or open-ended and do not exclude other unlisted elements or method steps. It should be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It should be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".
[0022] In addition, if the number of parts or components of the present application is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the value clearly indicates the singular.
[0023] The term "porous ceramic" used in this application refers to a ceramic material having a network structure composed of interconnected or closed pores.
[0024] Porous ceramic particles
[0025] The first aspect of the present application provides a porous ceramic particle, including: aluminum oxide, silicon oxide. The porous ceramic particles provided in the present application have suitable aluminum oxide and silicon oxide contents, and suitable porosity, so that they can be applied to the annealing process in the material preparation process. The porous ceramic particles still have good properties (for example, mechanical properties, thermal conductivity and health indicators, etc.) under high temperature conditions, so that the product quality of the annealing process can be guaranteed, and the service life can be improved, and it can also help reduce health risks, etc.
[0026] In one embodiment of the present application, the porous ceramic particles may have a suitable alumina content. Suitable alumina content can be beneficial to improve the performance of the porous ceramic particles. For example, based on the total weight of the porous ceramic particles, the content of alumina may be not less than about 20wt.%, not less than about 22wt.%, not less than about 24wt.%, not less than about 26wt.%, not less than about 28wt.%, not less than about 30wt.%, not less than about 32wt.%, not less than about 34wt.%, not less than about 36wt.%, not less than about 38wt.%, not less than about 40wt.%, not less than about 42wt.%, not less than about 44wt.%, not less than about 46wt.%, not less than about 48wt.%, not less than about 50wt.%, not less than about 52wt.%, not less than about 54wt.%, not less than about 56wt.%, not less than about 58wt.%, or not less than about 60wt.%. For another example, based on the total weight of the porous ceramic particles, the content of aluminum oxide may be no greater than about 70 wt.%, no greater than about 68 wt.%, no greater than about 66 wt.%, no greater than about 64 wt.%, no greater than about 62 wt.%, no greater than about 60 wt.%, no greater than about 58 wt.%, no greater than about 56 wt.%, no greater than about 54 wt.%, no greater than about 52 wt.%, or no greater than about 50 wt.%. Unless otherwise specified, the content of oxides (e.g., aluminum oxide (Al2O3), silicon oxide (SiO2), sodium oxide (Na2O), potassium oxide (KO), magnesium oxide (MgO), calcium oxide (CaO), titanium oxide (TiO2), iron oxide (Fe2O3), zirconium oxide (ZrO2), etc.) in the porous ceramic particles can be measured by X-ray fluorescence (XRF) analysis, and the specific measurement method can be referred to the embodiments of the present application.
[0027] In another embodiment of the present application, the porous ceramic particles can have a suitable silicon oxide content. Suitable silicon oxide content can be beneficial to improve the performance of the porous ceramic particles. For example, by the gross weight of the porous ceramic particles, the content of silicon oxide can be no more than about 75wt.%, no more than about 73wt.%, no more than about 71wt.%, no more than about 69wt.%, no more than about 67wt.%, no more than about 65wt.%, no more than about 63wt.%, no more than about 61wt.%, no more than about 59wt.%, or no more than about 57wt.%, no more than about 55wt.%, no more than about 53wt.%, no more than about 51wt.%, no more than about 49wt.%, no more than about 47wt.%, no more than about 45wt.%, no more than about 43wt.%, no more than about 41wt.%, no more than about 39wt.%, no more than about 37wt.%, or no more than about 35wt.%. For another example, based on the total weight of the porous ceramic particles, the silicon oxide content may be not less than about 25 wt.%, not less than about 27 wt.%, not less than about 29 wt.%, not less than about 31 wt.%, not less than about 33 wt.%, not less than about 35 wt.%, not less than about 37 wt.%, not less than about 39 wt.%, not less than about 41 wt.%, not less than about 43 wt.%, or not less than about 45 wt.%.
[0028] In another embodiment of the present application, porous ceramic particles can have suitable porosity. Suitable porosity can be conducive to improving the performance of porous ceramic particles. For example, the porosity of porous ceramic particles can be no more than about 70v / v%, no more than about 68v / v%, no more than about 66v / v%, no more than about 64v / v%, no more than about 62v / v%, no more than about 60v / v%, no more than about 58v / v%, no more than about 56v / v%, no more than about 54v / v%, no more than about 52v / v%, no more than about 50v / v%, no more than about 48v / v%, no more than about 46v / v%, no more than about 44v / v%, no more than about 42v / v%, or no more than about 40v / v%. For another example, the porosity of the porous ceramic particles may be not less than about 20 v / v%, not less than about 22 v / v%, not less than about 24 v / v%, not less than about 26 v / v%, not less than about 28 v / v%, not less than about 30 v / v%, not less than about 32 v / v%, not less than about 34 v / v%, not less than about 36 v / v%, not less than about 38 v / v%, not less than about 40 v / v%, not less than about 42 v / v%, not less than about 44 v / v%, not less than about 46 v / v%, not less than about 48 v / v%, or not less than about 50 v / v%. Unless otherwise specified, the porosity of the porous ceramic particles can be measured by the mercury intrusion method with reference to GB / T21650.1-2008, and the specific measurement method can refer to the embodiments of the present application.
[0029] In another embodiment of the present application, the porous ceramic particles may also include alkali metal oxides and / or alkaline earth metal oxides. The content of suitable alkali metal oxides and / or alkaline earth metal oxides may be beneficial to improve the performance of the porous ceramic particles. For example, by the total weight of the porous ceramic particles, the content of alkali metal oxides and / or alkaline earth metal oxides may be no more than about 10wt.%, no more than about 9wt.%, no more than about 8wt.%, no more than about 7wt.%, no more than about 6wt.%, no more than about 5wt.%, no more than about 4wt.%, no more than about 3wt.%, no more than about 2wt.%, or no more than about 1wt.%. For another example, the content of alkali metal oxides and / or alkaline earth metal oxides may be no less than about 2wt.%, no less than about 3wt.%, no less than about 4wt.%, no less than about 5wt.%, no less than about 6wt.%, no less than about 7wt.%, no less than about 8wt.%, or no less than about 9wt.%. In another embodiment of the present application, the alkali metal may be a combination of one or more of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), etc. In another embodiment of the present application, the alkaline earth metal may be a combination of one or more of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), etc.
[0030] In another embodiment of the present application, the porous ceramic particles may include a crystallized phase. The content of a suitable crystallized phase may be beneficial to improving the performance of the porous ceramic particles. For example, the crystallized phase may include a mullite phase, a quartz phase, an α-alumina phase, a crystalline free silica, etc. For another example, by the total weight of the porous ceramic particles, the content of the crystallized phase in the porous ceramic particles may be not less than about 30wt.%, not less than about 35wt.%, not less than about 40wt.%, not less than about 45wt.%, not less than about 50wt.%, not less than about 55wt.%, not less than about 60wt.%, not less than about 65wt.%, not less than about 70wt.%, or not less than about 75wt.%. For another example, based on the total weight of the porous ceramic particles, the content of the crystalline phase in the porous ceramic particles may be no greater than about 95 wt.%, no greater than about 90 wt.%, no greater than about 85 wt.%, no greater than about 80 wt.%, no greater than about 75 wt.%, no greater than about 70 wt.%, no greater than about 65 wt.%, no greater than about 60 wt.%, no greater than about 55 wt.%, or no greater than about 50 wt.%.
[0031] In another embodiment of the present application, porous ceramic particles may include an amorphous phase. The content of a suitable amorphous phase can be beneficial to improving the performance of porous ceramic particles. For example, by the gross weight of porous ceramic particles, the content of amorphous phase in porous ceramic particles may be not less than about 5wt.%, not less than about 10wt.%, not less than about 15wt.%, not less than about 20wt.%, not less than about 25wt.%, not less than about 30wt.%, not less than about 35wt.%, not less than about 40wt.%, or not less than about 45wt.%. For another example, by the gross weight of porous ceramic particles, the content of amorphous phase in porous ceramic particles may be not more than about 60wt.%, not more than about 55wt.%, not more than about 50wt.%, not more than about 45wt.%, not more than about 40wt.%, not more than about 35wt.%, not more than about 30wt.%, not more than about 25wt.%, or not more than about 20wt.%.
[0032] In another embodiment of the present application, the porous ceramic particles may include a mullite phase. The content of a suitable mullite phase may be beneficial to improving the performance of the porous ceramic particles. For example, by the total weight of the crystallized phase of the porous ceramic particles, the content of the mullite phase in the crystallized phase may be not less than about 30wt.%, not less than about 35wt.%, not less than about 40wt.%, not less than about 45wt.%, not less than about 50wt.%, not less than about 55wt.%, not less than about 60wt.%, not less than about 65wt.%, not less than about 70wt.%, not less than about 75wt.%, or not less than about 80wt.%. For another example, based on the total weight of the crystallized phase of the porous ceramic particles, the content of the mullite phase in the crystallized phase may be no greater than about 90 wt.%, no greater than about 85 wt.%, no greater than about 80 wt.%, no greater than about 75 wt.%, no greater than about 70 wt.%, no greater than about 65 wt.%, no greater than about 60 wt.%, no greater than about 55 wt.%, no greater than about 50 wt.%, no greater than about 45 wt.%, or no greater than about 40 wt.%. For another example, based on the total weight of the porous ceramic particles, the content of the mullite phase in the porous ceramic particles may be no less than about 10 wt.%, no less than about 15 wt.%, no less than about 20 wt.%, no less than about 25 wt.%, no less than about 30 wt.%, no less than about 35 wt.%, no less than about 40 wt.%, or no less than about 45 wt.%. For another example, based on the total weight of the porous ceramic particles, the content of the mullite phase in the porous ceramic particles may be no more than about 70 wt.%, no more than about 65 wt.%, no more than about 60 wt.%, no more than about 55 wt.%, no more than about 50 wt.%, no more than about 45 wt.%, no more than about 40 wt.%, no more than about 35 wt.%, no more than about 30 wt.%, or no more than about 25 wt.%. Unless otherwise specified, the content of the crystalline phase structure (e.g., crystalline phase, amorphous phase, mullite phase, quartz phase, α-alumina phase, crystalline free silica, etc.) in the porous ceramic particles can be measured by X-ray diffraction (XRD, X-Ray Diffraction) analysis, and the specific measurement method can be referred to the embodiments of the present application.
[0033] In another embodiment of the present application, the porous ceramic particles may include an α-alumina phase. The content of a suitable α-alumina phase may be beneficial to improving the performance of the porous ceramic particles. For example, based on the total weight of the crystallized phase of the porous ceramic particles, the content of the α-alumina phase in the crystallized phase may be not less than about 10wt.%, not less than about 15wt.%, not less than about 20wt.%, not less than about 25wt.%, not less than about 30wt.%, not less than about 35wt.%, not less than about 40wt.%, not less than about 45wt.%, not less than about 50wt.%, or not less than about 55wt.%. For another example, based on the total weight of the crystallized phase of the porous ceramic particles, the content of the α-alumina phase in the crystallized phase may be not greater than about 70 wt.%, not greater than about 65 wt.%, not greater than about 60 wt.%, not greater than about 55 wt.%, not greater than about 50 wt.%, not greater than about 45 wt.%, not greater than about 40 wt.%, not greater than about 35 wt.%, not greater than about 30 wt.%, not greater than about 25 wt.%, or not greater than about 20 wt.%. For another example, based on the total weight of the porous ceramic particles, the content of the α-alumina phase in the porous ceramic particles may be not less than about 5 wt.%, not less than about 10 wt.%, not less than about 15 wt.%, not less than about 20 wt.%, not less than about 25 wt.%, not less than about 30 wt.%, not less than about 35 wt.%, not less than about 40 wt.%, not less than about 45 wt.%, or not less than about 50 wt.%. For another example, based on the total weight of the porous ceramic particles, the content of α-alumina phase in the porous ceramic particles may be not greater than about 60 wt.%, not greater than about 55 wt.%, not greater than about 50 wt.%, not greater than about 45 wt.%, not greater than about 40 wt.%, not greater than about 35 wt.%, not greater than about 30 wt.%, not greater than about 25 wt.%, not greater than about 20 wt.%, or not greater than about 15 wt.%.
[0034] In another embodiment of the present application, the porous ceramic particles may include crystalline free silica. Suitable crystalline free silica can help improve the performance of the porous ceramic particles. The content of crystalline free silica in the porous ceramic particles is usually closely related to the content of crystalline free silica in the dust (e.g., silica dust, etc.) that may be generated during the use of the product, and is a key health indicator. For example, an increase in the content of crystalline free silica in the porous ceramic particles can lead to an increase in the content of crystalline free silica in the dust generated during the use of the product, thereby increasing the health risks caused by silica dust (e.g., the risk of contracting diseases such as silicosis), and vice versa, it can help reduce health risks. For another example, based on the total weight of the crystallized phase of the porous ceramic particles, the content of crystalline free silica in the crystallized phase may be no more than about 30 wt.%, no more than about 28 wt.%, no more than about 26 wt.%, no more than about 24 wt.%, no more than about 22 wt.%, no more than about 20 wt.%, no more than about 18 wt.%, no more than about 16 wt.%, no more than about 14 wt.%, no more than about 12 wt.%, no more than about 10 wt.%, no more than about 8 wt.%, no more than about 6 wt.%, no more than about 4 wt.%, no more than about 2 wt.%, or no more than about 1 wt.%. For another example, based on the total weight of the porous ceramic particles, the content of crystalline free silica in the porous ceramic particles may be no more than about 30 wt.%, no more than about 28 wt.%, no more than about 26 wt.%, no more than about 24 wt.%, no more than about 22 wt.%, no more than about 20 wt.%, no more than about 18 wt.%, no more than about 16 wt.%, no more than about 14 wt.%, no more than about 12 wt.%, no more than about 10 wt.%, no more than about 8 wt.%, no more than about 6 wt.%, no more than about 4 wt.%, no more than about 2 wt.%, or no more than about 1 wt.%.
[0035] In another embodiment of the present application, the porous ceramic particles may have a suitable average compressive strength. Suitable average compressive strength may be beneficial to improve the performance of the porous ceramic particles. For example, when the particle size of the porous ceramic particles meets not less than 1mm and not more than 2mm, the average compressive strength of the porous ceramic particles may be not less than about 40N, not less than about 45N, not less than about 50N, not less than about 55N, not less than about 60N, not less than about 65N, not less than about 70N, not less than about 75N, not less than about 80N, or not less than about 90N. For another example, when the particle size of the porous ceramic particles meets greater than 2mm and not more than 3.35mm, the average compressive strength of the porous ceramic particles may be not less than about 70N, not less than about 75N, not less than about 80N, not less than about 90N, not less than about 100N, not less than about 110N, not less than about 120N, or not less than about 130N. For another example, when the particle size of the porous ceramic particles satisfies greater than 3.35 mm and not greater than 4.75 mm, the average compressive strength of the porous ceramic particles may be not less than about 110 N, not less than about 120 N, not less than about 130 N, not less than about 140 N, not less than about 160 N, not less than about 180 N, and not less than about 200 N. For another example, when the particle size of the porous ceramic particles satisfies greater than 4.75 mm and not greater than 6.3 mm, the average compressive strength of the porous ceramic particles may be not less than about 160 N, not less than about 180 N, not less than about 200 N, not less than about 220 N, not less than about 240 N, not less than about 240 N, not less than about 260 N, or not less than about 280 N. For another example, when the particle size of the porous ceramic particles is greater than 6.3 mm, the average compressive strength of the porous ceramic particles may be not less than about 230 N, not less than about 240 N, not less than about 250 N, not less than about 260 N, not less than about 280 N, not less than about 300 N, not less than about 320 N, or not less than about 340 N. Unless otherwise specified, the average compressive strength of the porous ceramic particles can be measured by a UTS universal testing machine, and the specific measurement method can be referred to the embodiments of the present application.
[0036] In another embodiment of the present application, the porous ceramic particles may have a suitable bulk density. Suitable bulk density may be beneficial to improving the performance of the porous ceramic particles. For example, the bulk density of the porous ceramic particles may be not less than about 0.55 g / cm 3 , not less than about 0.6g / cm 3 , not less than about 0.65g / cm 3 , not less than about 0.7g / cm 3 , not less than about 0.75g / cm 3 , not less than about 0.8g / cm 3 , not less than about 0.85g / cm 3 , not less than about 0.9g / cm3 , or not less than about 0.95 g / cm 3 For another example, the porous ceramic particles may have a bulk density of no greater than about 1.2 g / cm 3 , not more than about 1.15g / cm 3 , not more than about 1.1g / cm 3 , not more than about 1.05g / cm 3 , not more than about 1g / cm 3 , not more than about 0.95g / cm 3 , not more than about 0.9g / cm 3 , not more than about 0.85g / cm 3 , or not more than about 0.8 g / cm 3 Unless otherwise specified, the bulk density of the porous ceramic particles can be measured and obtained with reference to YB / T 187-2001, and the specific measurement method can be found in the examples of this application.
[0037] In another embodiment of the present application, the porous ceramic particles may have a suitable particle size distribution. Suitable particle size distribution may be beneficial to improving the performance of the porous ceramic particles. For example, based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not more than 5.6 mm may be not less than about 50 wt.%, not less than about 52 wt.%, not less than about 54 wt.%, not less than about 56 wt.%, not less than about 58 wt.%, not less than about 60 wt.%, not less than about 62 wt.%, not less than about 64 wt.%, not less than about 66 wt.%, not less than about 68 wt.%, not less than about 70 wt.%, not less than about 72 wt.%, not less than about 74 wt.%, not less than about 76 wt.%, not less than about 78 wt.%, not less than about 80 wt.%, not less than about 82 wt.%, not less than about 84 wt.%, not less than about 86 wt.%, not less than about 88 wt.%, or not less than about 90 wt.%. For another example, based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not greater than 5.6 mm may be not greater than about 95 wt.%, not greater than about 94 wt.%, not greater than about 93 wt.%, not greater than about 92 wt.%, not greater than about 91 wt.%, not greater than about 90 wt.%, not greater than about 88 wt.%, not greater than about 86 wt.%, not greater than about 84 wt.%, not greater than about 82 wt.%, not greater than about 80 wt.%, not greater than about 78 wt.%, not greater than about 76 wt.%, not greater than about 74 wt.%, not greater than about 72 wt.%, or not greater than about 70 wt.%. For another example, based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not more than 3.35 mm may be not less than about 30 wt.%, not less than about 32 wt.%, not less than about 34 wt.%, not less than about 36 wt.%, not less than about 38 wt.%, not less than about 40 wt.%, not less than about 42 wt.%, not less than about 44 wt.%, not less than about 46 wt.%, not less than about 48 wt.%, not less than about 50 wt.%, not less than about 52 wt.%, not less than about 54 wt.%, not less than about 56 wt.%, not less than about 58 wt.%, or not less than about 60 wt.%.For another example, based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not more than 3.35 mm may be not more than about 70 wt.%, not more than about 68 wt.%, not more than about 66 wt.%, not more than about 64 wt.%, not more than about 62 wt.%, not more than about 60 wt.%, not more than about 58 wt.%, not more than about 56 wt.%, not more than about 54 wt.%, not more than about 52 wt.%, not more than about 50 wt.%, not more than about 48 wt.%, not more than about 46 wt.%, not more than about 44 wt.%, not more than about 42 wt.%, or not more than about 40 wt.%. Unless otherwise specified, the particle size distribution of the porous ceramic particles based on weight percentage can be measured and obtained with reference to YB / T 188-2001, and the specific measurement method can be referred to the embodiments of the present application.
[0038] In another embodiment of the present application, the porous ceramic particles can have a suitable particle size distribution. Suitable particle size distribution can be conducive to improving the performance of porous ceramic particles. For example, the D10 of porous ceramic particles can be not less than about 0.2mm, not less than about 0.3mm, not less than about 0.4mm, not less than about 0.6mm, not less than about 0.8mm, not less than about 1mm, not less than about 1.2mm, not less than about 1.4mm, not less than about 1.6mm, not less than about 1.8mm, not less than about 2mm or not less than about 2.2mm. For another example, the D10 of porous ceramic particles can be not more than about 3mm, not more than about 2.8mm, not more than about 2.6mm, not more than about 2.4mm, not more than about 2.2mm, not more than about 2mm, not more than about 1.8mm or not more than about 1.6mm. For another example, the D50 of the porous ceramic particles can be no less than about 1 mm, no less than about 1.2 mm, no less than about 1.4 mm, no less than about 1.6 mm, no less than about 1.8 mm, no less than about 2 mm, no less than about 2.2 mm, no less than about 2.4 mm, no less than about 2.6 mm, no less than about 2.8 mm, or no less than about 3 mm. For another example, the D50 of the porous ceramic particles can be no greater than about 5 mm, no greater than about 4.8 mm, no greater than about 4.6 mm, no greater than about 4.4 mm, no greater than about 4.2 mm, no greater than about 4 mm, no greater than about 3.8 mm, no greater than about 3.6 mm, no greater than about 3.4 mm, no greater than about 3.2 mm, or no greater than about 3 mm. For another example, the D90 of the porous ceramic particles can be no less than about 2 mm, no less than about 2.2 mm, no less than about 2.4 mm, no less than about 2.6 mm, no less than about 2.8 mm, no less than about 3 mm, no less than about 3.2 mm, no less than about 3.4 mm, no less than about 3.6 mm, no less than about 3.8 mm, no less than about 4 mm, no less than about 4.2 mm, no less than about 4.4 mm, no less than about 4.6 mm, no less than about 4.8 mm, or no less than about 5 mm. For another example, the D90 of the porous ceramic particles can be no greater than about 10 mm, no greater than about 9.6 mm, no greater than about 9.2 mm, no greater than about 8.8 mm, no greater than about 8.4 mm, no greater than about 8 mm, no greater than about 7.6 mm, no greater than about 7.2 mm, no greater than about 6.8 mm, no greater than about 6.4 mm, or no greater than about 6 mm. Unless otherwise specified, D10, D50 and D90 of porous ceramic particles can be measured based on volume percentage using camsizer equipment and supporting software from RETSCH Technology of Germany, in accordance with ISO13322-2. For specific measurement methods, see the examples of this application.
[0039] In another embodiment of the present application, porous ceramic particles can have a suitable pore size distribution. Suitable pore size distribution can be conducive to improving the performance of porous ceramic particles. For example, at least about 80v / v%, at least about 85v / v%, at least about 90v / v%, at least about 94v / v%, at least about 98v / v% or at least about 99v / v% of the porous ceramic particles can have a pore size of not less than about 5um, not less than about 7um, not less than about 9um, not less than about 11um, not less than about 13um, not less than about 15um, not less than about 17um, not less than about 19um, not less than about 21um, not less than about 23um, not less than about 25um, not less than about 27um, not less than about 29um, not less than about 31um, not less than about 33um or not less than about 35um. For another example, at least about 80 v / v%, at least about 85 v / v%, at least about 90 v / v%, at least about 94 v / v%, at least about 98 v / v%, or at least about 99 v / v% of the pores of the porous ceramic particles may have a pore size of no greater than about 50 um, no greater than about 48 um, no greater than about 46 um, no greater than about 44 um, no greater than about 42 um, no greater than about 40 um, no greater than about 38 um, no greater than about 36 um, no greater than about 34 um, no greater than about 32 um, no greater than about 30 um, no greater than about 28 um, no greater than about 26 um, no greater than about 24 um, no greater than about 22 um, or no greater than about 20 um. Unless otherwise specified, the pore size distribution of the porous ceramic particles can be measured by the mercury intrusion method with reference to GB / T21650.1-2008, and the specific measurement method can refer to the embodiments of the present application.
[0040] In another embodiment of the present application, the porous ceramic particles can have a suitable average pore size. Suitable average pore size can help improve the performance of the porous ceramic particles. For another example, the average pore size of the porous ceramic particles can be no less than about 8um, no less than about 10um, no less than about 12um, no less than about 14um, no less than about 16um, no less than about 18um, no less than about 20um, no less than about 22um or no less than about 24um. For another example, the average pore size of the porous ceramic particles can be no more than about 30um, no more than about 28um, no more than about 26um, no more than about 24um, no more than about 22um, no more than about 20um, no more than about 18um or no more than about 16um. Unless otherwise stated, the average pore size of the porous ceramic particles can be measured by the mercury intrusion method with reference to GB / T21650.1-2008, and the specific measurement method can refer to the present application embodiment.
[0041] In another embodiment of the present application, the porous ceramic particles may have a suitable average sphericity. Suitable average sphericity will help improve the performance of the porous ceramic particles. For another example, the average sphericity of the porous ceramic particles may be not less than about 0.7, not less than about 0.72, not less than about 0.74, not less than about 0.76, not less than about 0.78, not less than about 0.8, not less than about 0.82, not less than about 0.84, not less than about 0.86, not less than about 0.88, or not less than about 0.9. For another example, the average sphericity of the porous ceramic particles may be not more than about 0.95, not more than about 0.93, not more than about 0.91, not more than about 0.89, not more than about 0.87, or not more than about 0.85. Unless otherwise stated, the average sphericity of the porous ceramic particles can be measured by the camsizer equipment and supporting software of RETSCH Technology, Germany, with reference to ISO13322-2, and the specific measurement method can refer to the embodiment of the present application.
[0042] In another embodiment of the present application, the porous ceramic particles may have a suitable refractory temperature. Suitable refractory temperatures may be beneficial to improving the performance of the porous ceramic particles. For example, relatively high refractory temperatures may be beneficial to improving the performance of the porous ceramic particles at high temperatures, etc. For another example, the refractory temperature of the porous ceramic particles may be not less than about 1000°C, not less than about 1050°C, not less than about 1100°C, not less than about 1150°C, not less than about 1200°C, not less than about 1250°C, not less than about 1300°C, not less than about 1350°C, not less than about 1400°C, not less than about 1450°C, or not less than about 1500°C. For another example, the refractory temperature of the porous ceramic particles may be not more than about 1800°C, not more than about 1750°C, not more than about 1700°C, not more than about 1650°C, not more than about 1600°C, not more than about 1550°C, or not more than about 1500°C. Unless otherwise specified, the method for measuring the refractory temperature of porous ceramic particles can be found in the examples of this application.
[0043] In another embodiment of the present application, the porous ceramic particles may have a suitable thermal conductivity. Suitable thermal conductivity will be beneficial to improve the performance of the porous ceramic particles. For another example, the thermal conductivity of the porous ceramic particles at 400°C may be not less than about 0.15W / (m·℃), not less than about 0.17W / (m·℃), not less than about 0.19W / (m·℃), not less than about 0.21W / (m·℃), not less than about 0.23W / (m·℃), or not less than about 0.25W / (m·℃). For another example, the thermal conductivity of the porous ceramic particles at 400°C may be not more than about 0.3W / (m·℃), not more than about 0.28W / (m·℃), not more than about 0.26W / (m·℃), not more than about 0.24W / (m·℃), not more than about 0.22W / (m·℃), or not more than about 0.2W / (m·℃). For another example, the thermal conductivity of the porous ceramic particles at 1000°C may be not less than about 0.35 W / (m·°C), not less than about 0.37 W / (m·°C), not less than about 0.39 W / (m·°C), not less than about 0.41 W / (m·°C), not less than about 0.43 W / (m·°C), not less than about 0.45 W / (m·°C), not less than about 0.47 W / (m·°C), not less than about 0.49 W / (m·°C), not less than about 0.51 W / (m·°C), not less than about 0.53 W / (m·°C), or not less than about 0.55 W / (m·°C). For another example, the thermal conductivity of the porous ceramic particles at 1000°C may be no greater than about 0.65W / (m·°C), about 0.63W / (m·°C), about 0.61W / (m·°C), about 0.59W / (m·°C), about 0.57W / (m·°C), about 0.55W / (m·°C), about 0.53W / (m·°C), about 0.51W / (m·°C), about 0.49W / (m·°C), about 0.47W / (m·°C), or about 0.45W / (m·°C). Unless otherwise specified, the method for measuring the thermal conductivity of the porous ceramic particles can be found in the embodiments of the present application.
[0044] Raw material composition
[0045] The second aspect of the present application provides a raw material composition for preparing the porous ceramic particles provided in the first aspect of the present application. The raw material composition may include oxides and / or precursors thereof included in the porous ceramic particles (for example, substances that form corresponding oxides in the porous ceramic particles after being subjected to heat treatment). Each oxide in the porous ceramic particles is usually derived from each oxide and / or precursor corresponding thereto in the raw material composition, so the raw material composition can be adjusted according to the content of each oxide in the prepared porous ceramic particles. For example, one or more raw materials can be calcined (for example, 1000°C), and the content of each oxide in the calcined product can be measured using X-ray fluorescence analysis to calculate the amount of each oxide in the porous ceramic particles that can be provided by the raw material per unit mass (for example, 100g of raw material), so that each raw material can be matched in a suitable proportion according to the target content of each oxide in the porous ceramic particles to provide a raw material composition.
[0046] In one embodiment of the present application, the raw material composition may include alumina and / or its precursor, which may form the corresponding oxide (i.e., alumina) in the porous ceramic particles after heat treatment. As described above, alumina is a main component in the porous ceramic particles, and the raw materials may be matched in appropriate proportions according to the target content of alumina in the porous ceramic particles. In another embodiment of the present application, the alumina and / or its precursor in the raw material composition may come from a combination of one or more raw materials such as bauxite, pyroxene, clay, etc.
[0047] In one embodiment of the present application, the raw material composition may include silicon oxide and / or its precursor, which may form the corresponding oxide (i.e., silicon oxide) in the porous ceramic particles after being subjected to heat treatment. As described above, silicon oxide is a main component in the porous ceramic particles, and each raw material may be matched in a suitable proportion according to the target content of silicon oxide in the porous ceramic particles. In another embodiment of the present application, silicon oxide and / or its precursor in the raw material composition may come from one or more combinations of raw materials such as clay, bauxite, pyrope, albite, perlite, rice husk powder, etc.
[0048] In one embodiment of the present application, the raw material composition may include alkali metal oxides and / or their precursors, which may form corresponding oxides (i.e., alkali metal oxides) in the porous ceramic particles after heat treatment. As described above, the raw materials may be matched in appropriate proportions according to the target content of alkali metal oxides in the porous ceramic particles. In another embodiment of the present application, the alkali metal oxides and / or their precursors in the raw material composition may come from one or more combinations of raw materials such as clay, bauxite, and albite.
[0049] In one embodiment of the present application, the raw material composition may include alkaline earth metal oxides and / or their precursors, which may form corresponding oxides (i.e., alkaline earth metal oxides) in the porous ceramic particles after being subjected to heat treatment. As described above, each raw material may be matched in a suitable proportion according to the target content of alkaline earth metal oxides in the porous ceramic particles. In another embodiment of the present application, the alkaline earth metal oxides and / or their precursors in the raw material composition may come from one or more combinations of raw materials such as clay, bauxite, talcum powder, etc.
[0050] In another embodiment of the present application, the raw material composition may further include a pore former. The pore structure (e.g., pore size, porosity, etc.) of the porous ceramic particles is adjustable, for example, the pore structure of the porous ceramic particles can be adjusted by adjusting the pore former (e.g., the particle size of the pore former, the content of the pore former, the type of the pore former, etc.). In another embodiment of the present application, the pore former may be, for example, an inorganic pore former (e.g., perlite, etc.), an organic pore former (e.g., rice husk powder, etc.), or a combination of one or more thereof.
[0051] In another embodiment of the present application, the raw material composition may also include water and / or a binder. Porous ceramic particles need to have a suitable morphology (e.g., particle size, sphericity, etc.), which is closely related to the morphology of the precursor particles (e.g., particles that have not been heat treated). For example, the porous ceramic particles obtained after heat treatment can have a certain volume shrinkage compared to particles that have not been heat treated. For example, the volume shrinkage can be not less than about 10v / v%, not less than about 15v / v%, not less than about 20v / v%, not more than about 35v / v%, not more than about 30v / v%, or not more than about 25v / v%. The morphology of the precursor particles is adjustable, for example, the content of water and / or a binder, the type of a binder, etc., can be adjusted to adjust the water content, viscosity, etc. of the raw material composition, so that the morphology of the precursor particles can be adjusted. For example, the content of water in the raw material composition may account for no less than about 30wt.%, no less than about 35wt.%, no less than about 40wt.%, no more than about 60wt.%, no more than about 55wt.%, or no more than about 50wt.% of the total weight of the non-aqueous components in the raw material composition. For another example, based on the total weight of the raw material composition, the content of the binder in the raw material composition may account for no less than about 1wt.%, no less than about 2wt.%, no less than about 4wt.%, no more than about 10wt.%, no more than about 8wt.%, or no more than about 6wt.% of the total weight of the non-aqueous components in the raw material composition. For another example, the binder may be a combination of one or more of polyvinyl alcohol (PVA), polyethylene glycol (PEG), starch, etc.
[0052] Preparation method
[0053] The third aspect of the present application provides a method for preparing the porous ceramic particles provided in the first aspect of the present application, comprising the following steps: S1: providing precursor particles; S2: heat treatment. The raw material composition provided in the second aspect of the present application is formed to provide precursor particles, and the precursor particles are further heat treated to provide the above-mentioned porous ceramic particles.
[0054] In one embodiment of the present application, the present invention may include: molding the raw material composition provided in the second aspect of the present application to provide precursor particles. The raw material composition can be formed into precursor particles after a molding process. The morphology of the porous ceramic particles is usually related to the morphology of the precursor particles. Generally speaking, those skilled in the art can select a suitable molding process to provide the desired precursor particles through the above raw material composition. For example, it can be disc granulation, mixed granulation, etc.
[0055] In another embodiment of the present application, it may also include: heat treating the precursor particles to provide the above-mentioned porous ceramic particles. After the precursor particles are subjected to heat treatment, they can be sintered to form porous ceramic particles. Suitable heat treatment conditions can be beneficial to improving the properties of porous ceramic particles, for example, the performance of porous ceramic particles under high temperature conditions. In another embodiment of the present application, the heat treatment may include drying and / or sintering, etc. For example, drying may be performed at a temperature of not less than about 70°C, not less than about 75°C, or not less than about 80°C. For another example, drying may be performed at a temperature of not more than about 100°C, not more than about 95°C, not more than about 90°C, not more than about 55°C, or not more than about 80°C. For another example, sintering may be performed at a temperature of not less than about 1150°C, not less than about 1200°C, not less than about 1250°C, not less than about 1300°C, not less than about 1350°C, not less than about 1400°C, not less than about 1450°C, or not less than about 1500°C. For another example, sintering may be performed at a temperature of not greater than about 1600°C, not greater than about 1550°C, not greater than about 1500°C, not greater than about 1450°C, not greater than about 1400°C, not greater than about 1350°C, or not greater than about 1300°C.
[0056] Annealing medium
[0057] The fourth aspect of the present application provides an annealing medium, including the porous ceramic particles provided in the first aspect of the present application. The porous ceramic particles provided in the present application can be used as an annealing medium, which is suitable for the annealing process in the material preparation process. In the annealing process, the surface of the material to be annealed can usually be in direct contact with the sand mold (for example, furan resin sand mold, etc.), and the annealing medium is usually used to fill between the sand mold and the inner wall of the external container, so as to provide good support and appropriate heat conduction effect. The porous ceramic particles still have good performance (for example, mechanical properties, thermal conductivity and health indicators, etc.) under high temperature conditions, so as to ensure the product quality of the annealing process (for example, defects such as cracks of the product can be reduced, and the cracks of the product are usually generated during the cooling process), and can also have an improved service life (for example, the reusability of the annealing medium can be improved, etc.), and can also help reduce health risks (for example, the amount of dust generated by the annealing medium during use can be reduced, and the content of crystalline free silica in the annealing medium dust can be reduced, etc.). In one embodiment of the present application, the above-mentioned annealing medium can be applied to the annealing process in the preparation process of, for example, metal materials, non-metallic materials, etc. In another embodiment of the present application, the above annealing medium can be applied to the annealing process in the preparation process of refractory materials, etc. Examples of refractory materials can be refractory materials for glass kilns, etc., more specifically, fused zirconium corundum, etc.
[0058] The solution of the present application is further described in detail below in conjunction with specific embodiments.
[0059] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present application, and are not intended to limit the present application. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection created by the present application. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.
[0060] Example 1
[0061] Take 420g of pore-forming agent rice husk powder (SiO2 content 20-30wt.%), 400g of bauxite 80 (Al2O3 content 75-85wt.%), 125g of clay (Al2O3 content 20-40wt.%, SiO2 40-60wt.%), 55g of talcum powder (SiO2 content 50-65wt.%, MgO 25-40%), and 50g of starch. Place the above powders in the mixing tray of the granulator and mix them thoroughly. After the mixing is completed, increase the speed and slowly spray an appropriate amount of water into the mixture, and continue to observe the granulation during the process. Stop granulation when particles of suitable particle size are obtained. Take out the mixed granulated particles and put them in a tray, put them in an oven, and dry them. The dried granular material was placed in an alumina crucible, placed in a muffle furnace, heated to 1200°C at 5°C / min, and kept warm for 2 hours. After the heating was stopped, the sample was cooled with the furnace and then taken out to obtain Sample 1.
[0062] Example 2
[0063] Take 400g of pore-forming agent rice husk powder, 420g of bauxite 80, 130g of clay, 50g of albite powder (Na2O 8-13wt.%, SiO2 80-90wt.%), and 50g of starch. Place the above powders in the mixing pan of the granulator and mix them thoroughly. After the mixing is completed, increase the speed and slowly spray an appropriate amount of water into the mixture, and continuously observe the granulation during the process. After obtaining particles of suitable particle size, the granulation can be stopped. Take out the mixed granulated granular material and place it on a tray, put it in an oven, and dry it. The dried granular material is placed in an alumina crucible, placed in a muffle furnace, and heated to 1200℃ at 5℃ / min, kept warm for 2 hours. After the heating is stopped, the sample is cooled with the furnace and taken out to obtain sample 2. For the optical microscope photograph of the cross section of sample 2, see Figure 2 .
[0064] Example 3
[0065] A commercially available hollow sphere product was used as control sample 1, and its average particle size was 4 to 6 mm. The electron microscope photograph of the cross section of control sample 1 is shown in Figure 1 .
[0066] Take 420g of pore-forming agent rice husk powder, 400g of pyrope powder (Na2O, 8-13wt.%, Al2O335-45wt.%, SiO2 40-55wt.%), 125g of clay, and 55g of sodium feldspar powder. Place the above powders in the mixing plate of the granulator and mix them thoroughly. After the mixing is completed, increase the speed and slowly spray an appropriate amount of PEG aqueous solution into the mixture, and continuously observe the granulation during the process. After obtaining particles of suitable particle size, stop granulation. Take out the mixed granulated granular material and put it in a tray, put it in an oven, and dry it. The dried granular material is placed in an alumina crucible, placed in a muffle furnace, and heated to 1200℃ at 5℃ / min, and kept warm for 2 hours. After the heating stops, the sample is cooled with the furnace and taken out to obtain a trial sample.
[0067] Example 4
[0068] Oxide content (oxides)
[0069] 5 g of the sample to be tested was ground into powder with a mesh size of less than 200 by a disc mill, 1.2 g of the powder was weighed, mixed with 6 g of Li2B4O7, and melted to obtain a glass sheet. The content of oxides in each sample was detected by X-ray fluorescence analysis, and the test results are shown in Table 1. Samples 1 and 2 have higher alumina contents than the trial sample, and although the control sample 1 also has a relatively high alumina content, it is a hollow sphere structure.
[0070] Table 1
[0071]
[0072] Example 5
[0073] Phase structure
[0074] 10g of the sample to be tested was ground into powder below 200 mesh by disc milling, and the crystal phase composition of each sample was detected by X-ray diffraction analysis, instrument: X'Pert (PANalytical), analysis conditions: from 5° to 120° in 2θ, step of 0.0167°, 50s. The results were analyzed by High Score Plus software and ICDD (The International Centre for Diffraction Data) database, and the obtained test results are shown in Table 2. The test results in Table 2 are the weight percentage content given based on the total amount of the sample. The sample of the present application has a relatively high mullite content and a lower crystalline free silica content. Although the mullite content of the control sample 1 is also high, it is a hollow sphere structure.
[0075] Table 2
[0076]
[0077] Example 6
[0078] Single ball compressive strength
[0079] The compressive strength of a single spherical particle is tested by a UTS universal testing machine. During the measurement, a single spherical particle is placed on the loading platform of the UTS universal testing machine, and a 5kN load sensor is used with a moving rate of 0.5mm / min. After the sensor contacts the particle, it continues to apply pressure to the ceramic particle. When the ceramic particle is broken, the sensor no longer accelerates. At this time, the pressure value applied by the load sensor is recorded as the single ball compressive strength of the particle sphere.
[0080] Average compressive strength
[0081] The samples to be tested are screened using sieves with apertures of 1mm, 2mm, 3.35mm, 4.75mm, and 6.3mm to obtain samples within the target particle size range. Ten ceramic particles are randomly selected from the samples within the target particle size range obtained by screening. The single ball compressive strength of each ceramic particle is measured with reference to the above-mentioned single ball compressive strength measurement method. Among the ten test results obtained, the maximum value and the minimum value are removed respectively, and the single ball compressive strength test results of the remaining eight samples are averaged to calculate the average compressive strength of the sample to be tested within the particle size range.
[0082] Ten ceramic particles with a particle size between 4.75 and 6.3 mm were selected from the control sample 1, and the single ball compressive strength of each ceramic particle was measured by the above method. Among the test results of the 10 samples, the maximum and minimum values were removed respectively, and the test results of the remaining 8 samples were averaged to calculate the average compressive strength of the control sample 1 within the particle size range, which was specifically 148N.
[0083] Ten ceramic particles with a particle size between 1 and 2 mm, ten ceramic particles with a particle size between 2 and 3.35 mm, ten ceramic particles with a particle size between 3.35 and 4.75 mm, ten ceramic particles with a particle size between 4.75 and 6.3 mm, and ten ceramic particles with a particle size greater than 6.3 mm were selected from sample 2. The average compressive strength was tested by the above method. Among the test results of every 10 samples in each particle size range, one maximum value and one minimum value are removed respectively, and the test results of the remaining 8 samples are averaged to calculate the average compressive strength of sample 2 in each particle size range, specifically: the average maximum compressive strength of ceramic particles with a particle size between 1 and 2 mm is 72N; the average maximum compressive strength of ceramic particles with a particle size between 2 and 3.35 mm is 135N; the average maximum compressive strength of ceramic particles with a particle size between 3.35 and 4.75 mm is 250N; the average maximum compressive strength of ceramic particles with a particle size between 4.75 and 6.3 mm is 355N; the average maximum compressive strength of ceramic particles with a particle size of more than 6.3 mm is 500N. The obtained test results show that the samples of the present application have good average compressive strength.
[0084] Example 7
[0085] Loose packing density
[0086] Referring to YB / T 187-2001, a certain amount of the sample to be tested is placed in a fixed container of volume V, and the mass m2 of the sample to be tested is weighed, and the bulk density = m2 / V. The test results are shown in Table 3. The test results show that the sample of the present application has a higher bulk density.
[0087] Table 3
[0088]
[0089] Particle size distribution
[0090] Referring to YB / T 188-2001, the particle size distribution of the samples to be tested was measured using sieves with apertures of 0.5mm, 0.85mm, 1mm, 1.4mm, 1.7mm, 2mm, 2.8mm, 3.35mm, 4mm, 4.75mm, 5.6mm, and 6.3mm, respectively. The test results are shown in Table 4. It can be seen that about 60wt.% of the ceramic particles of sample 2 have a particle size between 1.4 and 3.35mm, and about 90wt.% of the ceramic particles have a particle size between 1.4 and 5.6mm. The particle size distribution is significantly wider than that of control sample 1 and the trial sample.
[0091] Table 4
[0092]
[0093] 100g of the sample to be tested was measured and characterized by the camsizer equipment and supporting software of RETSCH Technology of Germany according to ISO13322-2 based on volume percentage of the sample to be tested, and the measurement principle was digital imaging technology. The obtained test results showed that the sample of the present application had a wide particle size distribution.
[0094] Sphericity
[0095] 100g of the sample to be tested was measured and characterized according to ISO13322-2 by the camsizer equipment and supporting software of RETSCH Technology Company of Germany. The measurement principle is digital imaging technology. The characterization result of a single ceramic particle is the single sphere sphericity, and the characterization result of the sample to be tested as a whole is the average sphericity of the sample to be tested. The results are shown in Table 5. Although the control sample 1 has a high sphericity, it is a hollow sphere structure. The sample of this application has a relatively suitable sphericity.
[0096] Table 5
[0097] Control sample 1 Trial Sample Sample 2 Average sphericity 0.98 0.89 0.91
[0098] Porosity, average pore diameter and pore size distribution distribution)
[0099] By using a mercury intrusion instrument, 0.5 g of the sample to be tested is taken, and the porosity, average pore size and pore size distribution of the ceramic particles to be tested are determined by the mercury intrusion method according to GB / T21650.1-2008. The specific measurement conditions are as follows. The results are shown in Table 6:
[0100] Table 6
[0101]
[0102] Example 8
[0103] Refractoriness
[0104] Referring to the measurement method of particle size distribution in Example 7, measure the particle size distribution of 100g of the sample to be tested, and obtain a particle size range D1~D2 with a distribution amount of ~90wt.% of the total mass of the sample to be tested. Then, 100g of the sample to be tested is completely placed in a 2L alumina crucible and placed in a muffle furnace, and then the muffle furnace is heated to the target temperature (for example, 1300℃, 1350℃, 1400℃, etc.) at a heating rate of 5℃ / min, and kept warm for 4 hours. Then stop heating and let the sample cool with the furnace. After cooling, observe the sintering of the sample after heat treatment, and again refer to the measurement method of particle size distribution in Example 7 to sieve the obtained ceramic particles to obtain the distribution weight m3 of the sample after target temperature treatment in the particle size range D1~D2. Compare the changes in particle concentration of each sample to be tested after being subjected to the target temperature treatment, compare m3 with the distribution weight m4 of the initial sample to be tested in the particle size range D1-D2, and determine whether the change in m3 relative to m4 is less than 10wt.%. The highest target temperature that can reach the threshold requirement is the temperature of the refractoriness of the sample to be tested. The measurement results of each sample are shown in Table 7. It can be seen that the sample of the present application has good refractoriness.
[0105] Thermal conductivity
[0106] The thermal conductivity of the sample to be tested is tested by using an experimental furnace for testing thermal conductivity of amorphous refractory materials. The test uses a cylindrical furnace body, the material loading volume of the thermal conductivity furnace is 40L, and there is a heating tube in the middle of the furnace body. The radial heat flow meter is installed on the edge of the furnace body, and three thermocouples are inserted in the test medium at equal distances in the radial direction. After the sample to be tested is loaded into the furnace body, the temperature is raised to 400°C at a rate of 100°C / h and kept warm for 10 hours; then the temperature is continued to be raised to 800°C at a rate of 100°C / h and kept warm for 10 hours; the temperature is continued to be raised to 1000°C at a rate of 100°C / h and kept warm for 10 hours; the temperature is continued to be raised to 1200°C at a rate of 100°C / h and kept warm for 10 hours; the temperature is continued to be raised to 1300°C at a rate of 100°C / h and kept warm for 10 hours. After the experiment, the thermal conductivity is calculated by the following formula Among them, j+1 and j are two of the three thermocouples that are relatively closer to the center of the furnace. The measurement results of each sample are shown in Table 7. It can be seen that the sample of the present application has good thermal conductivity.
[0107]
[0108] Ф measure =Total flow calculated ieproduced measurement of the density flux multiplied by crossed surface
[0109] R j = Distance between thermocouple and center of equipment
[0110] T j = Temperature measured by thermocouple
[0111] Table 7
[0112]
Claims
1. A porous ceramic particle comprising: Alumina, wherein the content of the alumina is not less than 40 wt.% based on the total weight of the porous ceramic particles; Silicon oxide, wherein the content of the silicon oxide is not more than 55 wt.% based on the total weight of the porous ceramic particles; The porosity of the porous ceramic particles is not greater than 60 v / v%.
2. The porous ceramic particle according to claim 1, characterized in that The content of the aluminum oxide is no more than 70 wt. % based on the total weight of the porous ceramic particles.
3. The porous ceramic particle according to claim 1, characterized in that The content of the silicon oxide is not less than 25 wt. % based on the total weight of the porous ceramic particles.
4. The porous ceramic particle according to claim 1, characterized in that The porosity of the porous ceramic particles is not less than 30 v / v%.
5. The porous ceramic particle according to claim 1, characterized in that The porous ceramic particles further include alkali metal oxides and / or alkaline earth metal oxides.
6. The porous ceramic particle according to claim 5, characterized in that The content of the alkali metal oxide and / or alkaline earth metal oxide is not greater than 10 wt. % based on the total weight of the porous ceramic particles.
7. The porous ceramic particle according to claim 1, characterized in that The porous ceramic particles include a mullite phase, and the content of the mullite phase is not less than 10wt.% and not more than 70wt.% based on the total weight of the porous ceramic particles; And / or, the porous ceramic particles include an α-alumina phase, and the content of the α-alumina phase is not less than 5 wt.% and not more than 60 wt.%, based on the total weight of the porous ceramic particles.
8. The porous ceramic particle according to claim 1, characterized in that The porous ceramic particles include a mullite phase, and the content of the mullite phase is not less than 30wt.% and not more than 90wt.% based on the total weight of the crystallized phase of the porous ceramic particles; And / or, the porous ceramic particles include an α-alumina phase, and the content of the α-alumina phase is not less than 10 wt.% and not more than 70 wt.%, based on the total weight of the crystallized phase of the porous ceramic particles.
9. The porous ceramic particle according to claim 1, characterized in that The content of crystalline free silicon dioxide in the porous ceramic particles is not more than 30 wt.% based on the total weight of the crystal phase of the porous ceramic particles; And / or, the porous ceramic particles according to claim 1 are characterized in that the content of crystalline free silica in the porous ceramic particles is not more than 30 wt.%, based on the total weight of the porous ceramic particles.
10. The porous ceramic particle according to claim 1, characterized in that When the particle size of the porous ceramic particles is not less than 1 mm and not more than 2 mm, the average compressive strength of the porous ceramic particles is not less than about 50 N; and / or, When the particle size of the porous ceramic particles is greater than 2 mm and not greater than 3.35 mm, the average compressive strength of the porous ceramic particles is not less than 80 N; and / or, When the particle size of the porous ceramic particles is greater than 3.35 mm and not greater than 4.75 mm, the average compressive strength of the porous ceramic particles is not less than 120 N; and / or, When the particle size of the porous ceramic particles is greater than 4.75 mm and not greater than 6.3 mm, the average compressive strength of the porous ceramic particles is not less than 180 N; and / or, When the particle size of the porous ceramic particles is greater than 6.3 mm, the average compressive strength of the porous ceramic particles is not less than 250N.
11. The porous ceramic particle according to claim 1, characterized in that The bulk density of the porous ceramic particles is not less than 0.55 g / cm 3 , and not more than 1.2g / cm 3 .
12. The porous ceramic particle according to claim 1, characterized in that Based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not more than 5.6 mm is not less than 50 wt.% and not more than 95 wt.%; And / or, based on the total weight of the porous ceramic particles, the weight percentage of the porous ceramic particles having a particle size of not less than 1.4 mm and not more than 3.35 mm is not less than 30 wt.% and not more than 70 wt.%.
13. The porous ceramic particle according to claim 1, characterized in that At least 90 v / v% of the pores of the porous ceramic particles have a pore size of not less than 5 um and not more than 30 um.
14. The porous ceramic particle according to claim 1, characterized in that The average pore size of the porous ceramic particles is not less than 8 um and not more than 30 um.
15. The porous ceramic particle according to claim 1, characterized in that The average sphericity of the porous ceramic particles is not less than 0.7 and not more than 0.
95.
16. The porous ceramic particle according to claim 1, characterized in that The refractory temperature of the porous ceramic particles is not less than 1000°C, preferably not less than 1100°C, and more preferably not less than 1200°C.
17. The porous ceramic particle according to claim 1, characterized in that The thermal conductivity of the porous ceramic particles at 400° C. is not less than 0.15 W / (m·° C.) and not more than 0.3 W / (m·° C.).
18. The porous ceramic particle according to claim 1, characterized in that The thermal conductivity of the porous ceramic particles at 1000° C. is not less than 0.35 W / (m·° C.) and not more than 0.65 W / (m·° C.).
19. The method for preparing the porous ceramic particles according to any one of claims 1 to 18, comprising the following steps: S1: providing precursor particles; S2: Heat treatment.
20. Use of the porous ceramic particles according to any one of claims 1 to 18 as annealing media.
21. An annealing medium comprising the porous ceramic particles according to any one of claims 1 to 18.